PERSEPSI NASABAH AKAN LAYANAN ATM DAN E-BANKING DENGAN METODE TAM - Rinda Hesti Kusumaningtyas; Elsy Rahajeng (UIN Syarif Hidayatullah Jakarta, 2017)
ATM and e-banking is one of the technologies banking. E-banking is composed of Internet banking and SMS Banking. The general objective of this study was to determine the public perception of various people, especially banking customers will service ATM and e-banking. Methodology in this research using TAM as a tool to measure customer perception with data collection. Testing hypotheses using validity and reliability, the classic assumption test and multiple linear regression test. On the validity of all valid variable-value is above 0.1 the value of tolerance and reliability are worth reliable only. On normality test, graph plots obtained following the diagonal lines except the hypothesis interest income earned by the patterned plot graph and follow diagonal line. In multicolinearity test all variables does not occur multikolinearitas in getting out of tolerance values >0.1 and VIF <10. In the test heterokedastisitas on the graph plots the points obtained spreading pattern is not clear above and below the number 0 on the X axis and Y, except the hypothesis interest income earned by thepatterned plot graph below and above the Y. On Multiple Linear Regression Testing using R2 test, t test and F test results obtained independent variable significant effect on the dependent variable. From the results of hypothesis testing, it is known that the perception of the Customer will be ATM and e-banking methods TAM consisting of utilities/public works, Ease/PEU, Attitude/ATU, Interests/Biu, Technology/ATEU much influenced by variables of age and occupation. In the variable interest income was also influence each other.